Landschaft und Freizeit. Landschaftsbewertung als Grundlage für die Freizeitplanung in ländlichen Gebieten - Framke, Wolfgang (ERDKUNDE, 1981)
The article discusses the content and methodology of landscape evaluation, and is based upon the theoretical and empirical work carried out on leisure and recreation at the Geographical Institute, Aarhus University, over the last ten years. This discussion is linked to the Danish physical planning of the administration and the uses made of the landscape, as well as the associated interests (economic, environmental, recreative). The article describes and criticizes three efforts at landscape evaluation, that is those attempting to classify landscape from the viewpoint of its variation, its aesthetic impression and the preferences different social groups associate with the different landscapes. The conclusion drawn is that future landscape evaluation must be based upon the relationships between the individual groups’ actual social situation and the landscape as a commodity.